Growth of three-dimensional silver fractal electrodeposits under damped free convection - Carro, P. (1993)
Quasispherical three-dimensional Ag electrodeposits grown at constant potential and damped free convection exhibit a quasi-isotropic radial growth up to a critical radius rc≃0.3 cm and a mass fractal dimension DM=2.5. For r≫rc, DM→3. The product vrη’ is nearly constant, vr being the radial growth velocity, and η’ the apparent medium viscosity. It appears that vr is determined by the Laplacian field operating between cathode and anode.